Clinical Efficacy of Targeted Biologic Agents as Second-Line Therapy of Advanced Thyroid Cancer - Owonikoko, Taofeek K. (AlphaMed Press, 2013)
INTRODUCTION. Targeted biologic agents showed clinically meaningful efficacy as front-line therapy for advanced radioiodine-refractory and medullary thyroid cancer. The clinical benefit of these agents beyond the front line has yet to be established. METHODS. We assessed the clinical benefit of targeted agents in patients with advanced differentiated and medullary thyroid cancer treated at a single academic cancer center. We determined efficacy and compared front-line and second-line benefit using biochemical and anatomic response, time to treatment failure, and progression-free survival (PFS). Statistical differences were assessed by t test and chi-square test. Survival curves were generated by the Kaplan-Meier method. Differences in survival were assessed using the log-rank test, and a p value <.05 was considered significant. RESULTS. We identified 39 patients with advanced differentiated and medullary thyroid cancer treated with targeted biologic agents. Median age was 56.3 years. Overall, 25 men and 14 women participated. Histology showed 23% medullary and 77% differentiated cancer. Nineteen patients progressed on front-line therapy and subsequently received second-line therapy. Targeted agents conferred clinically meaningful benefit in the second-line setting in terms of biochemical response (13.3%), clinical benefit (83.3%), median time to treatment failure (4.0 months; 95% confidence interval: 2.6–8.2), and median PFS (4.6 months; 95% confidence interval: 3.2–8.2). Second-line benefit (median PFS) was more modest in comparison to the front-line setting in both genders (women: 3 months vs. 12.2 months; men: 6 months vs. 19.7 months), in differentiated cancers (4.1 months vs. 15.7 months), and with vascular targeting agents (4.4 months vs. 20.1 months). CONCLUSION. Patients with advanced thyroid cancer derived meaningful clinical benefit from additional therapy with a biologic agent following disease progression on front-line targeted therapy.